2020
DOI: 10.3390/ijgi9020066
|View full text |Cite
|
Sign up to set email alerts
|

Data Model for IndoorGML Extension to Support Indoor Navigation of People with Mobility Disabilities

Abstract: The increasing complexity of modern buildings has challenged the mobility of people with disabilities (PWD) in the indoor environment. To help overcome this problem, this paper proposes a data model that can be easily applied to indoor spatial information services for people with disabilities. In the proposed model, features are defined based on relevant regulations that stipulate significant mobility factors for people with disabilities. To validate the model’s capability to describe the indoor spaces in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Unlike objects in outdoor spaces that can be referenced with an absolute 2D coordinate system, indoor objects are usually described in 3D and referenced in relative terms by indoor spaces with a sematic meaning, such as rooms, corridors, or staircases [2,4]. Since the demand for spatial information about indoor spaces has been increasing in recent decades [3], many studies on modeling indoor spaces have been conducted and these can be divided into three categories: (1) data modeling of indoor spaces [3,21], (2) generation of indoor space models [22,23], and (3) applications of indoor space models [21]. Studies of the first category focus on expressing the indoor space with a data model, which conceptually supports the applications established by studies in the third category.…”
Section: Indoor Spaces For Emergency Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike objects in outdoor spaces that can be referenced with an absolute 2D coordinate system, indoor objects are usually described in 3D and referenced in relative terms by indoor spaces with a sematic meaning, such as rooms, corridors, or staircases [2,4]. Since the demand for spatial information about indoor spaces has been increasing in recent decades [3], many studies on modeling indoor spaces have been conducted and these can be divided into three categories: (1) data modeling of indoor spaces [3,21], (2) generation of indoor space models [22,23], and (3) applications of indoor space models [21]. Studies of the first category focus on expressing the indoor space with a data model, which conceptually supports the applications established by studies in the third category.…”
Section: Indoor Spaces For Emergency Responsementioning
confidence: 99%
“…A simulation model for real-world applications should be quantitatively correct in order to improve efficiency, capacity, and safety of evacuation. In another study discussing indoor navigation for disabled people, researchers found that the layout of ramps and stairs influences the mobility of wheelchair riders, and therefore a more accurate model of ramps and stairs is needed for in-depth analysis [21].…”
Section: Generation Of Stair Pathsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the benefits of developing an SDI are improved access to data, reduced duplication of effort in collecting and maintaining data, better availability of data, and interoperability between datasets. Although SDI development is an accepted task for most organizations and nations, and examples exist for various problem domains such as topographic mapping, indoor, health, marine, arctic, and so forth [65][66][67][68][69][70][71][72][73], attempts at developing data models for the improvement of disability rights are new within the literature [74]. As explained by Rajabifard et al [63], an SDI can be an enabling platform for sustainable development challenges.…”
Section: Use Of Geoinformation Tools and Technologies As Enablers Formentioning
confidence: 99%
“…No.Piso Storey number where the item is located Altura Architectural height of the element AlturaZ Altitude above sea level of the element Tipo The element is external or internal Function Type of navigation in the spaces: transition or general(applies to rooms only) Considering the characteristics or factors to be taken into account for the creation of navigation systems for people with mobility disabilities established by Park et al (2020) we assigned additional attributes in the room, door and stair layers. In the room layer with corridor function, we added width and slope.…”
Section: Attribute Descriptionmentioning
confidence: 99%